Evaluation and correlation of placental vasculature by three-dimensional power Doppler ultrasonography with umbilical Doppler in normal and IUGR pregnancies - Choudhary, Sumesh; Mishra, Vineet; Aggarwal, Rohina; Mistry, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In recent years there have been significant developments in the use of 3D Power Doppler (3DPD) imaging and quantitative 3DPD histogram analysis to estimate both placental volume and intraplacental vasculature. This study is to evaluate the distribution and variation of placental vascular indices according to gestational age and placental volume and position. Co relate the umbilical Doppler indices with placental vascular indices. Methods: From September 2016 to October 2017, three-dimensional (3D)-power Doppler ultrasound was performed in 200 singalton pregnancies from 20 to 40 weeks of gestation. Using the same pre-established settings for all patients, power Doppler was applied to the placenta and placental volume was obtained by the rotational technique (VOCAL). The 3D-power histogram was used to determine the placental vascular indices: vascularization index (VI), flow index (FI) and vascularization-flow index (VFI). Umbilical Doppler was measured on the free loop of umbilical cord. The placental vascular indices were then plotted against gestational age placental volume, position and umbilical Doppler SD ratio, PI and RI. These values were evaluated in IUGR fetus. Results: Analysis of the results showed that the placental vascular indices estimated by 3D-power Doppler ultrasonography presented constant distribution throughout gestation despite the significant increase in placental volume. Placental position at fundal region shows higher value of VI, FI, and VFI. Placental position with relation to VI, FI, and VFI shows statistically significant with p value <0.01. Placental vascular indices VI, FI and VFI when corelated with systolic/ diastolic ratio, pulsatility index and resistive resistance index of umbilical artery shows poor negative correlation, only VI and FI shows statistically significant with SD ratio as p value is <0.01and <0.04. VFI did not show statistically significant as p value is 0.10(NS). With pulsatility index p value is statistically significant is less than<0.01 with vascular indices. Resistive index p value is statistically significant is less than <0.01 for VI and VFI but not significant with FI as p value is 0.06. Conclusions: Doppler ultrasound assists in the evaluation of placental vascularization in normal and IUGR pregnancies, may play an important role in future research on fetoplacental insufficiency.